Increased genetic variation of bovine viral diarrhea virus in dairy cattle in Poland - Paweł Mirosław (BMC Veterinary Research, 2019)
Abstract Background Bovine viral diarrhea virus (BVDV) causes severe economic losses and is one of the most important viral pathogens of ruminants worldwide. The infection manifests itself in a variety of clinical symptoms. Phylogenetic studies based mainly on 5’UTR of its genome, identified many different subtypes of BVDV. Previous study indicated the predominance of BVDV-1b and BVDV-1d in Poland. The aim of this study was to genotype BVDV isolates currently circulating in Polish dairy herds. Results BVDV was detected in 30 herds. Viral subtypes were identified using sequences of the 5’UTR fragment and they were confirmed within a fragment of the Npro region. Seven subtypes of BVDV-1 species have been identified: 1b, 1 g, 1f, 1d, 1r, 1 s and 1e. Conclusion The number of subtypes of BVDV in Poland evolves and 2 new subtypes have been identified for the first time. Such studies may have a positive impact on successful eradication of the virus using effective vaccines and diagnostic tests.